Psychomotor development at 9 months of age in infants with perinatal asphyxia at the Mother and Child University Hospital of Libreville (Gabon) in 2023 - Mikolo, Aude M. L.; Maniaga, Raissa K.; Matoumba, Gessica M. N.; Tsafack, Jules; Nkama, Edmée M. M.; Mboungani, Morgane; Kamgaing, Eliane K.; Ategbo , Simon (International Journal of Contemporary Pediatrics, 2026)
Background: Perinatal asphyxia (PNA) is a common condition in neonatology. Objective of the study was to describe the short- and medium-term outcome of newborns presenting with PNA at the Centre Hospitalier Universitaire Mère-Enfant Fondation Jeanne Ebori (CHUME-FJE) in 2022. Methods: A prospective longitudinal and analytical study was conducted over a 16-month period. Newborns were included, regardless of gestational age, had presented with PNA. The statistical significance threshold was set at p<0.05. Results: 96/464 newborns hospitalized for PNA (20.7%). The sex ratio was 1.26. The mean resuscitation time was 9.1±7.1 min. Neurological complications accounted for 73.3% (n=63), with an AEI classified as Sarnat II (27.0%) and Sarnat III (22.2%). The mean hospital stay was 12.6 days. The overall death rate was 32.6%. During the course of the study, 50.0% of infants recovered to normal weight for their age at 9 months and a proportion of 7.7% presented with PML developmental delay and 11.5% with PCVM taking into account the corrected age for preterm newborns. Conclusion: APN remains a public health problem in sub-Saharan countries with high neonatal mortality and long-term neurodevelopmental sequelae. Prevention of this condition relies on better monitoring of pregnancy and delivery and a training program for healthcare personnel in newborn resuscitation in the delivery room.